Ferritin as a Marker of Severe Dengue in Children - Sekhar, Manchala Chandra (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: The aim is to evaluate ferritin levels in fever caused by dengue virus and their association with the severity of infection with dengue virus in children. Subjects and Methods: It is a Prospective that was done for 1 year in the department of pediatrics. 56 reported cases with a history of dengue fever for clinical evaluation by positive IgG and IgM antibodies and positive NS1 antigen and were included in the sample. All 16-year-old subjects with clinical dengue suspicion presenting in the department of emergency. Results: Out of total of 56 children with mean age of the children were 11.5 years and SD 3.5 years, and 59% were male who were majority. Mean hospital stay duration was 5 3 days. Most of the patients in study discharged in 5-7 days of admission in hospital. The mean serum ferritin levels among cases with DHF were raised than those with DF with significant p-values of< 0.05 on Day 5 and 6 of illness. During Days 5, 6, and 7 after the onset of fever, the results for sensitivity were 83, 86, and 92 per cent respectively. Conclusion: The incidence of hyperferritinaemia in patients infected with dengue virus is suggestive of highly active use of ferritin level in serum is 1,200 ng/ml as a method for predicting progression to DHF starting on Day 4 of the disease and continuing to recover.